1999
DOI: 10.1093/brain/122.10.1963
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation of medial temporal and frontal regions involved in processing novel and familiar words: an fMRI study

Abstract: Results of recent functional magnetic resonance imaging (fMRI) studies of memory are not entirely consistent with lesion studies. Furthermore, although imaging probes have identified neural systems associated with processing novel visual episodic information, auditory verbal memory using a novel/familiar paradigm has not yet been examined. To address this gap, fMRI was used to compare the haemodynamic response when listening to recently learned and novel words. Sixteen healthy adults (6 male, 10 female) learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
81
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 45 publications
14
81
1
1
Order By: Relevance
“…In agreement with earlier functional imaging studies demonstrating activation of the medial temporal lobe (hippocampus, parahippocampal gyrus, or both) in tasks of new learning (Stern et al, 1996;Tulving et al, 1996;Dolan and Fletcher, 1997;Gabrieli et al, 1997;Saykin et al, 1999;Strange et al, 1999), we found medial temporal activation only when subjects encountered the picture series for the first time. This finding agrees with our clinical data showing that patients who fail only in the new learning part of a continuous recognition task (first run) typically have medial temporal damage (Schnider et al, 1996c;Schnider and Ptak, 1999) and with a wealth of clinical studies demonstrating the importance of the medial temporal lobe for new learning (Scoville and Milner, 1957;Victor et al, 1961;DeJong et al, 1969;Zola-Morgan et al, 1986;Squire, 1992;Schnider et al, 1994;Mishkin et al, 1997;Nadel and Moscovitch, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with earlier functional imaging studies demonstrating activation of the medial temporal lobe (hippocampus, parahippocampal gyrus, or both) in tasks of new learning (Stern et al, 1996;Tulving et al, 1996;Dolan and Fletcher, 1997;Gabrieli et al, 1997;Saykin et al, 1999;Strange et al, 1999), we found medial temporal activation only when subjects encountered the picture series for the first time. This finding agrees with our clinical data showing that patients who fail only in the new learning part of a continuous recognition task (first run) typically have medial temporal damage (Schnider et al, 1996c;Schnider and Ptak, 1999) and with a wealth of clinical studies demonstrating the importance of the medial temporal lobe for new learning (Scoville and Milner, 1957;Victor et al, 1961;DeJong et al, 1969;Zola-Morgan et al, 1986;Squire, 1992;Schnider et al, 1994;Mishkin et al, 1997;Nadel and Moscovitch, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Regional cerebral blood flow (rCBF), measured during a yes/no recognition memory test, was higher for novel than for familiar items at a number of sites in the extended limbic system. Other research has corroborated the general thrust of these early findings [7,9,15,17,18], and has extended the novelty assessment networks to other cerebral regions beyond the limbic system, including a number of anterior and posterior neocortical sites [11,12,19]. We proposed a specific relation between novelty assessment and memory encoding in the form of a novelty encoding hypothesis.…”
Section: Introductionsupporting
confidence: 61%
“…As mentioned earlier, we selected the seed voxels for our analysis in the hippocampus because of considerable evidence in the literature about the involvement of the hippocampus in novelty detection [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]47]. It is also generally accepted that novelty detection involves regions beyond the hippocampus [ 1,2,12,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations